Identification of Ergonomic Principles of Housekeeping Work in Hospitality Services in Lovina, Bali - Wirawan, I Ketut Gede Agus Budi; Landra, Komang Gunawan; Widiarta, Made Bayu Oka (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Good hospitality service in hotel services in Lovina is highly expected. However, behind this, many hotel workers experience muscle complaints due to not working ergonomically or based on ergonomic principles. The purpose of this study was to identify the principles of ergonomic work in housekeeping in hotel services in Lovina Bali. The research method used was a quantitative descriptive method with the population being all housekeeping in hotels in Lovina Bali, samples taken by cluster random sampling of 42 housekeeping spread across starred and non-starred hotels in Lovina. The research instruments consisted of complete demographic data, knowledge, principles of ergonomic work and Nordic body map. The results of the study found that the principles of ergonomic work that had been implemented by HK in Lovina included reducing excessive workloads, placing equipment within reach, working according to body dimensions, reducing excessive movement, minimizing static movements, minimizing load points, having space distance, creating a comfortable environment and HK can reduce work stress. Meanwhile, according to the results of the analysis, HK has not been able to carry out workloads according to posture, perform ROM movements and make displays. The most common complaints measured using NMB are the neck, arms and calves. The conclusion is that there are still many HKs who do not understand the principles of work ergonomics, so there are several ergonomic points that have not been implemented properly.